Xyela fusca spec. nov. from Japan elucidates East Asian–North American relationships of Xyela (Hymenoptera, Xyelidae) - Blank, Stephan M.; Kramp, Katja; Shinohara, Akihiko (Zootaxa, 2017)
Morphological and genetic data indicate that Xyela fusca Blank, Kramp & Shinohara spec. nov. from Shikoku, Japan, plus an undescribed species from China are closely related to the Nearctic X. bakeri Konow, 1898. These species form the X. bakeri group, which is considered to be the sister clade of the Eurasian X. julii group. In addition to the X. alpigena group, the X. bakeri group is the second species group of Xyela with representatives occurring in both the Old and the New World. While X. bakeri is associated with Pinus (Pinus) species as the larval hosts, collection data of imagines suggest P. (Strobus) parviflora for X. fusca. This appears to be the second case, in which closely related Xyela species have switched hosts between species belonging to different subgenera of Pinus. Based on distribution data, migration of the common ancestor across Beringia appears likely, which would also have involved the change of the host subgenus. The six species of Xyela of Japan are keyed and new distribution data are presented. New, most northwesterly records of imagines from Yukon Territory (Canada) and field observations in Colorado and California (USA) suggest P. contorta as an additional larval host of X. bakeri.